5G's Role in the Data Communication Revolution - Efendi, Tino Feri (International Journal of Computer and Information System (IJCIS), 2025)
The 5G technology is an important milestone in the evolution of data communications by offering higher transmission speeds, lower latency, and greater network capacity. The implementation of 5G contributes to the improvement of data communication efficiency in various sectors, including industry, health, and transportation. This research aims to analyze the impact of 5G technology on data communication speed and reliability as well as the challenges in its implementation. The method used in this research is a literature study that refers to various academic sources related to the development of 5G and its application in data communication. The results show that 5G technology has great potential in improving network performance, although it still faces challenges in terms of infrastructure and security. Therefore, a proper strategy is needed in the implementation of 5G to maximize its benefits in data communication.